Apophatic Theology and Twentieth-Century Novels - Nisly, L. Lamar (Religion and the arts, 2018)
Drawing on apophatic theology, this essay argues that some twentieth-century texts invite an apophatic approach by revealing the limits of language and hinting at some understanding of God, without doing so directly. First, Leif Enger's Peace Like a River shows a divine encounter but, in the process, underscores the limits of language to describe this experience. Second, in a sort of parallel to negative theology, Walker Percy’s Lancelot points readers toward God by having Lancelot descend into sin and evil, an affirmation of God through negation. Finally, in Joseph Heller’s Catch-22, a novel without explicit Christian interests, characters parody prayer, rail against the world’s unfairness, and deny God, but in these interactions they actually reveal something about belief and God. These texts reveal that an apophatic understanding can enrich our reading of twentieth-century novels.